Antimicrobial Activity and Synergism of Lactoferrin and Lysozyme Against Cariogenic Microorganisms - Andrade,Flaviana Bombarda de (2014)
The present study evaluated the antimicrobial in vitro effects of the salivary proteins lactoferrin and lysozyme on microorganisms involved in the carious process, obtaining their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Streptococcus mutans (ATCC 25175) and Lactobacillus casei (ATCC 7469) were submitted to broth macrodilution of lysozyme at 80 mg/mL and lactoferrin at 200 mg/mL. The tubes were read in a spectrophotometer after they had been incubated at 37 °C for 18 h, in a carbon dioxide chamber, in order to read the MIC. A new subculture was carried on agar plates to obtain the MBC. The agar diffusion method was also tested, using BHI agar with 100 µL of the standardized microbial inocula. Filter-paper disks soaked in 10 µL of the solutions lactoferrin (200 µg/mL) and lysozyme (80 µg/mL) were placed on the agar surface. Inhibition halos were not observed on the plates, showing the absence of the antimicrobial effects of these proteins in this method. The bactericidal and bacteriostatic effects of lysozyme on L. casei were 50.3 mg/mL and 43.1 mg/mL respectively. The bactericidal and bacteriostatic effects on S. mutans were 68.5 mg/mL and 58.7 mg/mL. Lactoferrin did not induce any inhibitory effects on any microorganism, even in the concentration of 200 mg/mL. There was not a synergic antimicrobial effect of proteins, when they were tested together, even in the concentration of 42.8 mg/mL of lysozyme and 114 mg/mL of lactoferrin (the highest values evaluated). S. mutans and L. casei were only inhibited by lysozyme, not affected by lactoferrin and by the synergic use of both proteins.